IL-9 neutralizing antibody suppresses allergic inflammation in ovalbumin-induced allergic rhinitis mouse model - Zhao, He; Gu, Zhaowei; Wang, Yunxiu; Wang, Meng; Zhan, Yue; Zhao, Xin; Cao, Zhiwei (Frontiers in Pharmacology, 2022)
Allergic rhinitis is mainly mediated by IgE after specific individuals are exposed to allergens. It is a common nasal mucosa disease of non-infectious chronic inflammatory disease and is often accompanied by asthma and conjunctivitis. In the study of allergic asthma, it was found that IL-9 participates in the pathogenic development of asthma. Because asthma and allergic rhinitis have the same airway and the same disease, it is inferred that IL-9 may also play an important role in allergic rhinitis. BALB/c mice received intranasal stimulation of ovalbumin (OVA) treatment at different times. The nasal mucosa of the mice were then sliced and stained with Sirius red and Toluidine blue, and eosinophils and mast cells in the mucosa were counted. ELISA was used to detect the expression of OVA-IgE in peripheral blood. The Th2 cell fraction in the mouse spleen was detected by flow cytometry. The expressions of IL-4, IL-5, IL-9, and IL-13 and their mRNA in mucosa were detected by real-time PCR and flow cytometry bead array analysis. Finally, the expression changes of Thymic stromal lymphopoietin related proteins and its mRNA, JAK1/2, and STAT5 proteins were detected by real-time PCR and Western blot. After the intervention with the IL-9 neutralizing antibody, the symptoms of allergic rhinitis in mice were significantly reduced. The expression of OVA-IgE in the peripheral blood of mice was inhibited, the fraction of Th2 cells in the spleen decreased, the related cytokines (IL-4, IL-5, and IL-13) were inhibited, and their functions decreased. The TSLP-OX40/OX40L signal pathway and JAK1/2-STAT5 signal are inhibited. IL-9 neutralizing antibody has a good therapeutic effect on the mouse model of allergic rhinitis, which may be related to the TSLP-OX40/OX40L pathway and JAK1/2-STAT5 signaling.